2009
DOI: 10.1177/1363461509102292
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Experience of Psychotropic Treatment

Abstract: Despite growing concern over the treatment of adolescents with psychiatric medications, little research has examined youth understandings and interpretations of mental illness and psychotropic treatment. This article reports the exploratory findings of semi-structured and open-ended interviews carried out with 20 adolescents diagnosed with one or more psychiatric disorders, and who were currently prescribed psychiatric medications. Grounded theory coding procedures were used to identify themes related to adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 37 publications
3
58
0
1
Order By: Relevance
“…Carpenter-Song, 2009;Ecks, 2010;Oldani, 2009;Singh, 2004;Floersch et al, 2009;Timimi and Taylor, 2004;McKinney and Greenfield, 2010;Weinberg, 1997;Barnett, 2012b). Psychiatric medications are both material and discursive agents As such, the use of medications is part of local processes of identity construction and positioning that are inscribed within larger discourses, institutional structures, and political-economies of psychiatry and psychopharmacology (Blackman, 2007).…”
Section: A Clinical Ethnographic Study: Medications As Vehicles Of Somentioning
confidence: 95%
“…Carpenter-Song, 2009;Ecks, 2010;Oldani, 2009;Singh, 2004;Floersch et al, 2009;Timimi and Taylor, 2004;McKinney and Greenfield, 2010;Weinberg, 1997;Barnett, 2012b). Psychiatric medications are both material and discursive agents As such, the use of medications is part of local processes of identity construction and positioning that are inscribed within larger discourses, institutional structures, and political-economies of psychiatry and psychopharmacology (Blackman, 2007).…”
Section: A Clinical Ethnographic Study: Medications As Vehicles Of Somentioning
confidence: 95%
“…Bentley (2010) conducted a qualitative research study with 21 adults with serious mental illness and found seven themes around medication being a pervasive positive force, a tolerated fact of life, an internal and individual experience, a prominent part of the story and evolution of one's mental illness, a basis of gratitude and source of victory over past struggles, a necessary protection of a personal sense of humanness, and a symbol of differentness and dependency. Floersch et al (2009) studied children and adolescents and found that themes of expectation and hope were especially prominent among the youth.…”
Section: Medication and Neurobiologymentioning
confidence: 98%
“…2. Interviews conducted were based on the Teen Subjective Experience of Medication (TeenSEMI), a semi-structured interview instrument (Floersch et al 2009), which the authors modified to accomodate and reflect the experiences of college-age participants. The present study is embedded in a larger ethnographic study that includes interviews conducted with teenagers ages 14-18 about their medication experiences, their parents, and mental health practitioners, and from participation in and observations made of a QueÂŽbec hospital emergency mental health team during that time period.…”
mentioning
confidence: 99%